A re-sequencing based assessment of genomic heterogeneity and fast neutron-induced deletions in a common bean cultivar - O'Rourke, Jamie A.; Iniguez, Luis P.; Bucciarelli, Bruna; Roessler, Jeffrey; Schmutz, Jeremy; McClean, Phillip E.; Jackson, Scott A.; Hernandez, Georgina; Graham, Michelle A.; Stupar, Robert M.; Vance, Carroll P. (Frontiers in Plant Science, 2013)
A small fast neutron mutant population has been established from Phaseolus vulgaris cv. Red Hawk. We leveraged the available P. vulgaris genome sequence and high throughput next generation DNA sequencing to examine the genomic structure of five Phaseolus vulgaris cv. Red Hawk fast neutron mutants with striking visual phenotypes. Analysis of these genomes identified three classes of structural variation; between cultivar variation, natural variation within the fast neutron mutant population, and fast neutron induced mutagenesis. Our analyses focused on the latter two classes. We identified 23 large deletions (>40 bp) common to multiple individuals, illustrating residual heterogeneity and regions of structural variation within the common bean cv. Red Hawk. An additional 18 large deletions were identified in individual mutant plants. These deletions, ranging in size from 40 bp to 43,000 bp, are potentially the result of fast neutron mutagenesis. Six of the 18 deletions lie near or within gene coding regions, identifying potential candidate genes causing the mutant phenotype.